Evaluation of Stepping Stones as a tool for changing knowledge, attitudes and behaviours associated with gender, relationships and HIV risk in Karnataka, India - Ramesh Banadakoppa M; Bhattacharjee Parinita; Bradley Janet E; Girish Meghna; Das Arup K (BMC, 2011)
Abstract Background Stepping Stones training aims to help individuals explore sexual relationships and recognize gender inequalities, the structural drivers of the HIV epidemic, in order to understand risk behaviours and to seek solutions to factors that increase HIV vulnerability. Despite earlier studies suggesting the success of Stepping Stones, little data exist to show diffusion to trainees' social networks or the wider community. Methods A mixed-methods evaluation of this approach was undertaken using in-depth interviews of trainees and friends, and polling booth surveys in 20 villages where Stepping Stones training took place and in another 20 villages with no Stepping Stones intervention. Results The interview respondents and their friends reported significant changes in their relationships after training, and benefit from discussion of gender, sexuality, condom use and HIV vulnerability issues. However, though diffusion of this knowledge at the level of personal contacts was strong, the evaluation revealed that diffusion to the community level was limited. Conclusions The qualitative part of this study reflects other studies in different settings, in that SS participants gained immensely from the training. Wider behaviour change is a challenging goal that many programmes fail to attain, with most interventions too limited in scope and intensity to produce larger community effects. This may have contributed to the fact that we observed few differences between interventions and non-intervention villages in this study. However, it is also possible that we had excessive expectations of individual change at the community level, and that it might have been more appropriate to have had broader community level rather than individual behavioural change indicators. We suggest that SS could be enhanced by efforts to better engage existing community opinion leaders, to empower and train participants as community change agents, and to support the development of village-level action plans that combat sexual stereotyping and risky behaviours that lead to unhealthy sexual relationships.